Kajian Behavioral Setting pada Interior Café di Surabaya - Mellisa Mellisa; I Gusti Ngurah Ardana; Sherly De Yong (Intra, 2017)
This research is done to find out cafe consumer’s behavior, who visit cafe’s as a public space to do various activities. The benchmarks used to analyze the different behaviors is the behavioral setting theory. The method used to collect correct data is behavioral mapping method. The data obtained from cafes located in West, Central and East Surabaya were analyzed using behavioral components which are physical properties, social components, and the environmental setting. The result of the analysis shows that consumers in Antler Cabin Cafe West Surabaya and Konig Coffee and Bar East Surabaya start to shift towards service which depends on staff’s cafe. While consumers in Titik Koma Coffee and Calibre Coffee Roasters Central Surabaya, tend to not depend on the cafe’s staff because they perform self-service.